2022
DOI: 10.7554/elife.72898
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory alkalosis provokes spike-wave discharges in seizure-prone rats

Abstract: Hyperventilation reliably provokes seizures in patients diagnosed with absence epilepsy. Despite this predictable patient response, the mechanisms that enable hyperventilation to powerfully activate absence seizure-generating circuits remain entirely unknown. By utilizing gas exchange manipulations and optogenetics in the WAG/Rij rat, an established rodent model of absence epilepsy, we demonstrate that absence seizures are highly sensitive to arterial carbon dioxide, suggesting that seizure-generating circuits… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 109 publications
(136 reference statements)
2
8
0
Order By: Relevance
“…1 ). The pattern of this c-Fos expression in the BK-D434G MLT mirrors what was observed in another rodent model for absence seizures, the WAG/Rij rat, in which the seizures were triggered by hypoxia-induced hyperventilation 45 . These findings suggest that the role of the MLT in absence seizures is not limited to the context of the BK-D434G mutation.…”
Section: Discussionsupporting
confidence: 75%
“…1 ). The pattern of this c-Fos expression in the BK-D434G MLT mirrors what was observed in another rodent model for absence seizures, the WAG/Rij rat, in which the seizures were triggered by hypoxia-induced hyperventilation 45 . These findings suggest that the role of the MLT in absence seizures is not limited to the context of the BK-D434G mutation.…”
Section: Discussionsupporting
confidence: 75%
“…Another way of alpha2-mediated upregulation of HCN channels is cellular alkalinization [ 132 ] which shifts I h activation potential to more depolarized values [ 133 ]. A recent study showed that in rats genetically predisposed to absence epilepsy, spike-wave activity can be triggered by hypoxia-induced blood alkalosis resulting in the activation of neurons in the intralaminar thalamic nuclei [ 134 ].…”
Section: Cellular Targets Of Alpha2 Ars In Relation To Spike-wave Act...mentioning
confidence: 99%
“…The phase and depth of respiration has a well-established connection to epilepsy [27][28][29] , in contrast to other physiological brain pulsations 28 . In routine EEG diagnostics, hyperventilation reduces epileptic seizure threshold and increases neuronal excitability, and is thus routinely used to provoke seizure activity during recording session in patients with epilepsy, even though the underlying mechanisms remain unknown 56 . The increased power of respiratory brain pulsations detected in epileptic brains may similarly affect the CSF solute transport, alter neuronal excitability thus lowering the seizure threshold 28 , especially given the tendency for both slower and reversed impulse propagation (Figs.…”
Section: Discussionmentioning
confidence: 99%